Meningkatkan Proses dan hasil Belajar Siswa pada tema Selamatkan Makhluk Hidup dengan Metode Ekplorasi Lingkungan Sekitar pada Siswa Kelas VI - Desrina Desrina (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
The background of this research is that science learning has been theoretical without students knowing how the application of learning in everyday life and learning Science does not encourage students to care about the environment so students cannot know the process of a natural event in living things, such as plants. the author wants students to be closer to nature and at the same time can increase the process and learning outcomes, especially those related to science. The approach used is a qualitative approach. The research data was obtained from the results of the assessment of learning implementation plan (RPP), the results of the observation sheet on the implementation of learning with the Approach to Environmental Exploration Approach from the aspects of teachers, students and evaluation. The data source is the process of implementing the Neighborhood Exploration approach to the theme of Saving Sentient Beings in class VI of SD Negeri 23 Painan Utara. The results of the study are the learning of Science with the Approach to the Environmental Environment Exploration will lead to an attitude of student concern for the environment, motivating students to learn. This is evidenced by the increase in student learning outcomes, namely cycle I completeness of students 61% with an average value of 73 and cycle II completeness of students 83% with an average value of 84. Based on the results of the study, it is suggested to the following parties (1) for teachers The Neighborhood Exploration approach in learning Science because it can cause students to care about the environment and improve student learning outcomes, (2) the reader should be able to add knowledge to the reader.